Structural Insights Into the Transcriptional Regulation of HigBA Toxin–Antitoxin System by Antitoxin HigA in Pseudomonas aeruginosa - Liu, Ying; Gao, Zengqiang; Liu, Guangfeng; Geng, Zhi; Dong, Yuhui; Zhang, Heng (Frontiers in Microbiology, 2020)
HigB-HigA is a bacterial toxin-antitoxin (TA) system in which the antitoxin HigA can mask the endoribonuclease activity of toxin HigB and repress the transcription of the TA operon by binding to its own promoter region. The opportunistic pathogen Pseudomonas aeruginosa HigBA (PaHigBA) is closely associated with the pathogenicity by reducing the production of multiple virulence factors and biofilm formation. However, the molecular mechanism underlying HigBA TA operon transcription by PaHigA remains elusive. Here, we report the crystal structure of PaHigA binding to the promoter region of higBA operon containing two identical palindromic sequences at 3.14 Å resolution. The promoter DNA is bound by two cooperative dimers to essentially encircle the intact palindrome region. The helix-turn-helix (HTH) motifs from the two dimers insert into the major grooves of the DNA at the opposite sides. The DNA adopts a canonical B-DNA conformation and all the hydrogen bonds between protein and DNA are mediated by the DNA phosphate backbone. A higher resolution structure of PaHigA-DNA complex at 2.50 Å further revealed three water molecules bridged the DNA-binding interface and mediated the interactions between the bases of palindromic sequences and PaHigA (Thr40, Asp43 and Arg49). Structure-based mutagenesis confirmed these residues are essential for the specific DNA-binding ability of PaHigA. Our structure-function studies therefore elucidated the cooperative dimer-dimer transcription repression mechanism, and may help to understand the regulation of multiple virulence factors by PaHigA in P. aeruginosa.